Comparison of Effect of Pilates exercise and Vitex agnus intake on Premenstrual Syndrome in sedentary girls - Samadi, Zeinab (Health Nexus, 2026)
Context: Premenstrual-syndrome (PMS) is one of the most common problems in women during their childbearing age. It has negative effects on their work performance and the quality of their lives. This study aimed to study Comparison of Effect of Pilates exercise and Vitex agnus intake on Premenstrual Syndrome in sedentary girls. Materials and Methods: This quasi-experimental study was conducted on 60 sedentary adult girl students aged 18-25 at Isfahan University, with a diagnosis of PMS. The instruments included personal information and a medical questionnaire, a form of premenstrual symptoms DSM‑IV, the GHQ 28 questionnaire, and the Beck Depression and Anxiety questionnaire, and also, daily symptoms were recorded for 4 months. After collecting personal and medical information, the participants were allocated to two experimental groups (Pilates exercise and Vitex agnus) and a control group. Assessments were performed during the first-third menstrual periods (pre-test, mid-test, and post-test, respectively). One way and repeated measures analysis of variance (ANOVA) were used to analyze the data. Results: Results showed that the mean scores of PMS and symptoms declined after 2 months of training in the experimental group. In both experimental groups, the mean scores of PMS and physical and psychological symptoms decreased after one and two months (P<0.001). Also, the results indicate that the mean score in decreasing physical, psychological symptoms and total score in Pilates was more than Vitex agnus and control group (P<0.001). Conclusions: Overall, the findings showed that 2 months of Pilates exercise is effective in preventing the symptoms of PMS and can be used as a treatment.